Antecedents of Career Success: Proactive Perspective - Gari, Susan; Purnomo, Ratno; Indrayanto, Adi (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2023)
The main aim of the present study was to examine the impact proactive behavior has on career success in an individual context. The study also emphasised two antecedents,that is, proactive personality and management support by which employees engage in proactive behavior. Descriptive research design has been used in the study. Stratified random sampling method was used in the study. The study dtermined to conduct the data collection with 30 respondents from Royal Papuan Yacht club.The study shows the significant correlation between proactive behavior, proactive personality, management support and career success..